Factors affecting genotyping success in giant panda fecal samples - Ying Zhu; Hong-Yi Liu; Hai-Qiong Yang; Yu-Dong Li; He-Min Zhang (PeerJ, 2017)
Fecal samples play an important role in giant panda conservation studies. Optimal preservation conditions and choice of microsatellites for giant panda fecal samples have not been established. In this study, we evaluated the effect of four factors (namely, storage type (ethanol (EtOH), EtOH −20 °C, 2-step storage medium, DMSO/EDTA/Tris/salt buffer (DETs) and frozen at −20 °C), storage time (one, three and six months), fragment length, and repeat motif of microsatellite loci) on the success rate of microsatellite amplification, allelic dropout (ADO) and false allele (FA) rates from giant panda fecal samples. Amplification success and ADO rates differed between the storage types. Freezing was inferior to the other four storage methods based on the lowest average amplification success and the highest ADO rates (P < 0.05). The highest microsatellite amplification success was obtained from either EtOH or the 2-step storage medium at three storage time points. Storage time had a negative effect on the average amplification of microsatellites and samples stored in EtOH and the 2-step storage medium were more stable than the other three storage types. We only detected the effect of repeat motif on ADO and FA rates. The lower ADO and FA rates were obtained from tri- and tetra-nucleotide loci. We suggest that freezing should not be used for giant panda fecal preservation in microsatellite studies, and EtOH and the 2-step storage medium should be chosen on priority for long-term storage. We recommend candidate microsatellite loci with longer repeat motif to ensure greater genotyping success for giant panda fecal studies.